Non-cash compensation with production externalities and agency problems related to an agent's consumption choice - Adithipyangkul, Pattarin (Elsevier Ltd, 2012)
This paper considers remuneration in terms of a good that helps improve or facilitate production in an agency paradigm. In the presence of this production externality, agency problems arise when the agent has an access to an external market for the good or has private, pre-contract information about the production environment. This paper characterises the optimal compensation packages in a variety of settings. The research findings explain various pay practices, such as payment in terms of reimbursement for a certain good and the selective payment of non-cash compensation.